Respuesta :
Now that's a complete question! lol
P(-8,6) -> P'(-10,2)
means we add -2 to x, and -4 to y, the rule is
(x,y) -> (x-2, y-4)
Check: P'(-8-2,6-4)=P'(-10,2)..... ok.
P(-8,6) -> P'(-10,2)
means we add -2 to x, and -4 to y, the rule is
(x,y) -> (x-2, y-4)
Check: P'(-8-2,6-4)=P'(-10,2)..... ok.
Answer with explanation:
The coordinate of point P in x-y Plane= (-8,6)
Coordinate of point in the same plane after translation = P'(-10,2)
→Abscissa in Pre image + (-2)= Abscissa in Image
-8 +(-2)= -10
Abscissa is shifted Horizontally left Direction by 2 units.
→Ordinate in Pre image + (-4)= Ordinate in Image
6 +(-4)= 2
Ordinate is shifted Vertically down by 4 units.